PENGARUH PENGGUNAAN MEDIA CHATGPT DENGAN METODE TUTOR SEBAYA TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI KELAS X SMA NEGERI 1 SIANTAR TAHUN AJARAN 2025/2026 - Tambunan, Yesica Febrianti; Sianipar, Herlina Hotmadinar; Siahaan, Tumpal Manahara (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to determine the effect of using ChatGPT media with the peer tutoring method on the economics learning outcomes of Grade X students at SMA Negeri 1 Siantar in the 2025/2026 academic year. The background of this study was the low learning outcomes in economics, where 68.5% of students had not achieved the Minimum Mastery Criteria (KKM). This research used a quantitative approach with a quasi-experimental design in the form of a Nonequivalent Control Group Design. The population consisted of 337 Grade X students of SMA Negeri 1 Siantar. The samples were selected using cluster sampling technique, namely class X-1 as the experimental class consisting of 35 students and class X-2 as the control class consisting of 32 students. Data collection techniques included tests in the form of pre-test and post-test as well as documentation. The research instrument consisted of 20 multiple-choice questions that had been validated. The results showed that the average post-test score of the experimental class was 8.75, which was higher than the control class score of 5.73. The hypothesis testing using the t-test showed that tcount was 4.12 and ttable was 1.68 at a significance level of α = 0.05. Since tcount > ttable (4.12 > 1.68), Ha was accepted and H0 was rejected. Therefore, the use of ChatGPT media with the peer tutoring method had a significant effect on students’ economics learning outcomes.